2020
DOI: 10.1371/journal.pone.0227983
|View full text |Cite
|
Sign up to set email alerts
|

Association between regular exercise and asthma control among adults: The population-based Northern Finnish Asthma Study

Abstract: Previously those with asthma were often advised to avoid strenuous exercise because of fear for exercise-induced asthmatic reactions, but recent findings suggest many beneficial effects on health related to exercise. We elaborated on the relation between regular exercise and asthma control among adults. This was a population-based cross-sectional Northern Finnish Asthma Study (NoFAS), in which altogether 1922 adult subjects 17-73 years old living in Northern Finland answered the NoFAS questionnaire. The determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The cardiopulmonary fitness level is correlated with the ACQ 6 score, indicating that those with uncontrolled asthma had the lowest level of fitness score and probably also the lowest level of activity. These findings confirm that exercise training is associated with better asthma control, which is supported by former research in the field [ 4 , 5 , 15 , 17 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The cardiopulmonary fitness level is correlated with the ACQ 6 score, indicating that those with uncontrolled asthma had the lowest level of fitness score and probably also the lowest level of activity. These findings confirm that exercise training is associated with better asthma control, which is supported by former research in the field [ 4 , 5 , 15 , 17 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 89%
“…Another more recent review including 11 studies and 543 adult participants with asthma found a significant improvement in FEV1 induced by exercise training [ 4 ]. Exercise-induced bronchospasm (EIB) has long been thought to be part of the explanation of the lower level of PA among patients with asthma [ 16 ], but two systemic reviews suggest that exercise training in patients with stable asthma would not cause EIB limitations [ 15 , 17 ]⁠.…”
Section: Introductionmentioning
confidence: 99%
“…Although benefits of exercise training for asthma control have already been described for children (34), we were not able to find studies comparing exercise capacity between children with controlled or uncontrolled STRA. An association of exercise and control of asthma has already been demonstrated in a large population-based study in adults (35). In addition, in children, a recent study has shown that asthmatic patients with uncontrolled asthma achieved a decreased distance in the 6-min walk test when compared to controlled subjects, although no information on disease severity of patients was provided (36).…”
Section: Discussionmentioning
confidence: 98%
“…It seems possible that shorter temporal exposure to the disease, impaired airway remodeling, and use of modern pharmacotherapy may help explain these findings in pediatric samples (37)(38)(39)(40)(41). In asthmatic patients, pulmonary function impairment appears to become more relevant in early adulthood, which may be associated with an excessively labile bronchomotor tone in children with STRA, thereby explaining the few spirometric changes even in the presence of frequent symptoms (35).…”
Section: Discussionmentioning
confidence: 99%
“…This article compared methods for the imputation of a semi-continuous variable in a context where it is analyzed as a categorical exposure variable as is commonly done in epidemiological analyses. [43][44][45][46] We examined three methods that imputed ordinal categories directly, and six methods that imputed the semi-continuous variable followed by categorization. Across the simulation scenarios, we found that the ordinal logistic regression and ZINB imputation approaches performed well across most scenarios.…”
Section: Discussionmentioning
confidence: 99%